Analysis of service satisfaction factors in the internal medicine polyclinic of a general hospital: A cross-sectional study - Wiladatika; Ali Harokan; Lilis Suryani (Lentera Perawat, 2025)
Background: Patient satisfaction is a key indicator for evaluating the quality of health care services. Various factors can influence patient satisfaction, ranging from demographic characteristics to attributes of public service delivery. However, studies on patient satisfaction in the Internal Medicine Outpatient Clinic at Kepahiang District General Hospital remain limited. Objective: This study aimed to analyze the factors associated with the level of patient satisfaction with services in the Internal Medicine Outpatient Clinic at Kepahiang District General Hospital in 2025. Methods: This research employed a quantitative analytic design with a cross-sectional approach. A total of 98 respondents were selected through purposive sampling. Data were collected using a structured questionnaire that had been tested for validity and reliability. Data analysis included chi-square tests for bivariate associations and multiple logistic regression for multivariate analysis with a significance level of α = 0.05. Results: The findings revealed that all service-related variables—requirements, procedures, service completion time, costs/fees, service product specifications, staff competence, staff behavior, complaint handling, and facilities and infrastructure—were significantly associated with patient satisfaction (p < 0.05). The dominant factors influencing patient satisfaction were staff competence and staff behavior, both of which were strongly related to patients’ experiences in receiving care. Conclusion: Patient satisfaction is influenced by the synergy of all service aspects; therefore, quality improvement efforts must be comprehensive, integrative, and sustainable. This study recommends that hospitals strengthen the competence of health care providers, improve facilities and infrastructure, and simplify administrative processes to enhance patient satisfaction.